2021
DOI: 10.3390/cancers13020177
|View full text |Cite
|
Sign up to set email alerts
|

CD73, Tumor Plasticity and Immune Evasion in Solid Cancers

Abstract: Regulatory networks controlling cellular plasticity, important during early development, can re-emerge after tissue injury and premalignant transformation. One such regulatory molecule is the cell surface ectoenzyme ecto-5′-nucleotidase that hydrolyzes the conversion of extracellular adenosine monophosphate to adenosine (eADO). Ecto-5′-nucleotidase (NT5E) or cluster of differentiation 73 (CD73), is an enzyme that is encoded by NT5E in humans. In normal tissue, CD73-mediated generation of eADO has important ple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 150 publications
0
34
0
Order By: Relevance
“…Unlike the majority of solid cancer types, the expression of CD73 in cervical tumours is decreased in comparison to normal tissue. 34,35 Interestingly, the same is observed in other tumours of the genitourinary system, for example, ovarian serous cystadenocarcinoma, testicular germ cell tumours, endometrial carcinoma, uterine carcinosarcoma, bladder carcinoma, kidney chromophobe and prostate adenocarcinoma. 35 Therefore, the similarity of our results analysing cervical tumour spheres in vitro with data from these two recent studies of bioinformatics shows that the CSC model is capable to represent some characteristics of the in vivo tumours.…”
Section: Discussionmentioning
confidence: 60%
“…Unlike the majority of solid cancer types, the expression of CD73 in cervical tumours is decreased in comparison to normal tissue. 34,35 Interestingly, the same is observed in other tumours of the genitourinary system, for example, ovarian serous cystadenocarcinoma, testicular germ cell tumours, endometrial carcinoma, uterine carcinosarcoma, bladder carcinoma, kidney chromophobe and prostate adenocarcinoma. 35 Therefore, the similarity of our results analysing cervical tumour spheres in vitro with data from these two recent studies of bioinformatics shows that the CSC model is capable to represent some characteristics of the in vivo tumours.…”
Section: Discussionmentioning
confidence: 60%
“…For example, the extracellular metabolism of ATP into adenosine through the CD38-NPP1-CD73 axis, the CD39-CD73 axis, and the NDPK/NME/NM23 axis is well-documented target system for tumor treatment [32]. CD73 could be a critical regulator that promotes tumor progression in an immune-independent manner, such as tumor stemness, epithelial-tomesenchymal transition (EMT), and therapy resistance [32,33]. Our data supported the concept that CD73-induced generation of adenosine promotes the Warburg effect and tumor growth in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…AP deregulation in cancer has been principally linked to ADO accumulation in the TME that promotes regulatory T-cells (Tregs) activity and polarization of myeloid cells to immunosuppressive and pro-angiogenic phenotypes and affects NKs and effector T cells (CD8+), thus enhancing tumor growth. Many studies have reported that increased expression of CD73 in cancer relates to different outcomes, such as progression, poor prognosis, metastasis, and weak response to chemotherapy agents [ 116 ]. Although ADO signaling has been poorly investigated in MPM, available data support a role for AP in MPM immune-suppression.…”
Section: Mesothelioma Microenvironment Crosstalk: Molecular Mechanismsmentioning
confidence: 99%